Implementation of the Ca-Score Method to Assess the Financial Performance of Agricultural Sector Companies in Indonesia - Arma Yuliza; Fefti Yulian Mela; Susanti (CV Edujavare Publishing, 2026)
This study aims to analyze the condition of financial distress as an indicator of financial performance for agricultural sector companies listed on the Indonesia Stock Exchange (IDX). A quantitative descriptive approach was employed, utilizing secondary data—specifically the financial statements of agricultural sector companies—obtained from the official IDX website and the companies' own financial reports. The analysis utilized the CA-Score model, which assesses financial condition based on the ratios of shareholders' investment to assets, earnings before tax and financial expenses to assets, and sales to assets. The results indicate that among the 12 sampled companies, three (25%)—Daya Guna Samudra Tbk. (DGSA), Nusa Palapa Gemilang Tbk. (NPGF), and Jaya Agra Wattie Tbk. (JAWA)—recorded CA-Score values ​​above 0.30, thereby categorizing them as experiencing financial distress. Meanwhile, the remaining nine companies (75%) fell into the non-financial distress category. The findings suggest that while the majority of agricultural sector companies maintain a relatively sound financial condition, certain companies require attention regarding the improvement of profitability, asset utilization efficiency, and capital structure management to minimize the risk of future financial distress.